A gel single ion conducting polymer electrolyte enables durable and safe lithium ion batteries via graft polymerization. Issue 70 (30th November 2018) - Chen, Yazhou; Xu, Guodong; Liu, Xupo; Pan, Qiyun; Zhang, Yunfeng; Zeng, Danli; Sun, Yubao; Ke, Hanzhong; Cheng, Hansong
Abstract : A post-grafting strategy to synthesize single ion conducting polymer electrolytes for lithium metal secondary batteries. Abstract : Concentration polarization issues and lithium dendrite formation, which associate inherently with the commercial dual-ion electrolytes, restrict the performance of lithium ion batteries. Single ion conducting polymer electrolytes (SIPEs) with high lithium ion transference numbers ( t + ≈ 1) are being intensively studied to circumvent these issues. Herein, poly(ethylene- co -vinyl alcohol) (EVOH) is chosen as the backbone and then grafted with lithium 3-chloropropanesulfonyl(trifluoromethanesulfonyl)imide (LiCPSI) via Williamson's reaction, resulting in a side-chain-grafted single ion polymer conductor (EVOH- graft -LiCPSI). The ionomer is further blended with poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) by solution casting for practical use. The SIPE membrane with ethylene carbonate and dimethyl carbonate (EC/DMC = 1 : 1, v/v) as plasticizer ( i.e., gel SIPE) exhibits an ionic conductivity of 5.7 × 10 −5 S cm −1, a lithium ion transference number of 0.88, a wide electrochemical window of 4.8 V ( vs. Li/Li + ) and adequate mechanical strength. Finally, the gel SIPE is applied in a lithium ion battery as the electrolyte as well as the separator, delivering an initial discharge capacity of 100 mA h g −1 at 1C which remains at 95 mA h g −1 after 500 cycles.